2017
DOI: 10.1016/j.clcc.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to Fatigue Management in Colorectal Cancer

Abstract: Cancer-related fatigue is serious and complex, as well as one of the most common symptoms experienced by patients with colorectal cancer, with the potential to compromise quality of life, activities of daily living, and ultimately survival. There is a lack of consensus about the definition of cancer-related fatigue; however, definitions have been put forward by the European Association for Palliative Care (EAPC) and the National Comprehensive Cancer Network (NCCN). Numerous cancer- and treatment-related factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 101 publications
(118 reference statements)
2
42
0
5
Order By: Relevance
“…Fatigue among cancer survivors is thought to have a multifactorial etiology. Fatigue has been associated with treatment (radio-and chemotherapy), stage of disease, presence of (multiple) comorbidities, specific medications with sedating side effects, psychological factors (e.g., depression), decreased physical activity, and malnutrition [2,[5][6][7]. Several studies investigated whether there was an association between obesity and fatigue among cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue among cancer survivors is thought to have a multifactorial etiology. Fatigue has been associated with treatment (radio-and chemotherapy), stage of disease, presence of (multiple) comorbidities, specific medications with sedating side effects, psychological factors (e.g., depression), decreased physical activity, and malnutrition [2,[5][6][7]. Several studies investigated whether there was an association between obesity and fatigue among cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Forty per cent of patients report cancer‐related fatigue (CRF) at diagnosis, and 80%–90% experience treatment‐related fatigue (Aapro, Scotte, Bouillet, Currow, & Vigano, 2017; Berger, Mooney, & CB, 2019; Koornstra, Peters, Donofrio, van den Borne, & de Jong, 2014). The causes of CRF are multiple and complex, and the specific mechanisms have not all been identified (Aapro et al., 2017; Berger et al., 2019). It has been widely reported that CRF directly affects quality of life and survival in cancer (Aapro et al., 2017; Berger et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The causes of CRF are multiple and complex, and the specific mechanisms have not all been identified (Aapro et al., 2017; Berger et al., 2019). It has been widely reported that CRF directly affects quality of life and survival in cancer (Aapro et al., 2017; Berger et al., 2019). The VICAN 5 (INCa, 2018) study showed that if a patient's needs 6 months after the diagnosis are not successfully managed during the treatment period, they are likely to have a long‐term impact on outcomes (INCa, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations